Bauxite mining activities at Bukit Goh, Kuantan, Pahang, Malaysia: concerns of residents to radiation exposure from naturally occurring radioactive substances - Hayat, Norshuhadah; Sayed, Inayatullah Shah (IIUM Press, International Islamic University Malaysia, 2018)
Bauxite mining in Kuantan district of Pahang has raised health concerns of communities residing near the mining areas. Bauxite mining and transportation activities have contributed a lot to the pollution of environment. There is a fear among the residents of the areas that whether the soil is free from naturally occurring radioactive substances or not. Therefore, the objective of this study was to detect the presence of natural radioactive elements in the soil of bauxite mining field at Bukit Goh, Kuantan. Soil samples were gathered from various locations of Bukit Goh. These samples were dried for twenty-four hours and cleared of stones and pebbles. The soil then was crushed and ground to a fine powder, and heated in the oven for two hours to ensure the soil was dried completely. Samples were packed/sealed in plastic bags, labelled and stored for a month to achieve secular equilibrium. The Advanced Nuclear Spectroscopy System with UCS 30 Universal Computer Spectrometer Software and High Sensitivity Gamma Spectroscopy Model SE-9764 with WinDas Software were used for recording the energy spectrum of each soil sample. Comparison of the spectra of all soil samples was made with the background measurement and no difference was found from each other. In conclusion, no naturally occurring radioactive substances were found in the soil of bauxite mining area at Bukit Goh, Kuantan. Therefore, the soil poses no radiation exposure related health hazards to the residents of the areas of Bukit Goh, Kuantan.